1974
DOI: 10.1002/cne.901580404
|View full text |Cite
|
Sign up to set email alerts
|

The upper layers of the superior colliculus of the rat: A Golgi study

Abstract: A number of questions deriving from a previous electron microscopic study of the superficial layers of the rat superior colliculus pointed out the need for a comprehensive study of the cell types of the superior colliculus and their detailed morphology. In the present Golgi study the cells of the superficial layers of the superior colliculus were found to be of five major types; marginal cells, horizontal cells, narrow field vertical cells, wide field vertical cells, and stellate cells. Some of these categorie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
135
1

Year Published

1978
1978
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 203 publications
(167 citation statements)
references
References 29 publications
10
135
1
Order By: Relevance
“…The staining pattern in these animals was also very similar to the pattern described in control animals SC (non operated) (data not shown). In normal animals we have demonstrated that (Tenório et al 1996), a sub-population of all the different cell types described with the Golgi staining in the rat SC (Langer and Lund 1974) expressed NOS (Tenório et al 1996). The same cell types were also stained in both deafferented and afferented SC of the ablated animals.…”
Section: Resultsmentioning
confidence: 53%
“…The staining pattern in these animals was also very similar to the pattern described in control animals SC (non operated) (data not shown). In normal animals we have demonstrated that (Tenório et al 1996), a sub-population of all the different cell types described with the Golgi staining in the rat SC (Langer and Lund 1974) expressed NOS (Tenório et al 1996). The same cell types were also stained in both deafferented and afferented SC of the ablated animals.…”
Section: Resultsmentioning
confidence: 53%
“…As previously indicated, the optical layer is continuous with the brachium of the superior colliculus, which in turn is a continuation of the optic tract, as will be more fully described below. The medial gray layer is a layer of cell bodies principally of the multipolar variety (Langer & Lund, 1974). While the major portion of the medial gray layer is typically considered with the deeper, nonvisual, layers of the superior colliculus, certain investigators have noted the termination of both retinofugal and corticofugal fibers in this layer, at least in Nautastained material.…”
Section: General Considerationsmentioning
confidence: 99%
“…The description of cell types within the superior colliculus rests upon Golgi-prepared material, with the most recent description offered by the excellent observations of Langer and Lund (1974). However, while the descriptions provided by Langer and Lund are most detailed, they are, in one sense, somewhat difficult to become accustomed to since they are referenced to Cajal's zonal organization of the superior colliculus.…”
Section: Intrastructural Morphology Cellular Morphologymentioning
confidence: 99%
See 1 more Smart Citation
“…We could not recover or had to discard morphological data for the remaining 21 neurons because labeling was not observed in 6 cases, it was too faint to trace dendritic arbors in 5 cases, or 2 or more neurons were labeled in 10 cases (although only 1 neuron was targeted in each of those recordings). Based on the location of soma and somatodendritic morphologies (Langer and Lund, 1974; Tokunaga and 15 Otani, 1976;Labriola and Laemle, 1977;Mooney et al, 1985Mooney et al, , 1988Edwards et al, 2002), we classified the labeled neurons into 7 types ( Fig. 2A), including wide-field vertical (WFV; n = 4; Fig.…”
mentioning
confidence: 99%